Investment Interest in the Islamic Capital Market: The Role of Investment Knowledge, Return Perception, and Pocket Money Management - Sonia, Lailatul Izzah; Solekah, Nihayatu Aslamatis (Universitas Islam Kadiri, 2025)
This study is motivated by the growing investment interest among Generation Z, despite persistently low levels of Islamic financial literacy, particularly in Malang City. The research examines the influence of investment knowledge, perception of return, and pocket-money management on investment interest in the Islamic capital market. A quantitative approach was employed, distributing questionnaires to 166 Generation Z respondents residing in Malang. Data were analysed with SPSS version 25.0 through instrument validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroskedasticity), and multiple-linear-regression analysis. The results show that all three independent variables, both individually and simultaneously, have a significant effect on investment interest. Among them, pocket-money management emerges as the most dominant factor. These findings underscore the importance of enhancing Islamic financial literacy, shaping realistic return expectations, and strengthening young people’s ability to manage their pocket money as strategic efforts to boost their participation in the Islamic capital market.